2013
DOI: 10.1021/bi3016185
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Experimental Model for Protein Evolution: Effects of Mutation Rate and Selection Stringency on Evolutionary Outcomes

Abstract: Protein evolution is a critical component of organismal evolution and a valuable method for the generation of useful molecules in the laboratory. Few studies, however, have experimentally characterized how fundamental parameters influence protein evolution outcomes over long evolutionary trajectories or multiple replicates. In this work, we applied phage-assisted continuous evolution (PACE) as an experimental platform to study evolving protein populations over hundreds of rounds of evolution. We varied evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 58 publications
(112 reference statements)
2
43
0
Order By: Relevance
“…Here the evolving molecule, usually T7 RNA polymerase, is repeatedly selected for high activity inside E. coli cells, allowing for the completion of hundreds of evolution rounds within a few days. With this technique, populations that were evolved under low selection stringency followed by high selection stringency reproducibly arrived at different sets of mutations than when evolution was done at high stringency alone, similar to the results of our study (69). Additionally, low selection stringency generated larger genetic diversity, which appeared to be the case in our study as well.…”
Section: Discussionsupporting
confidence: 87%
“…Here the evolving molecule, usually T7 RNA polymerase, is repeatedly selected for high activity inside E. coli cells, allowing for the completion of hundreds of evolution rounds within a few days. With this technique, populations that were evolved under low selection stringency followed by high selection stringency reproducibly arrived at different sets of mutations than when evolution was done at high stringency alone, similar to the results of our study (69). Additionally, low selection stringency generated larger genetic diversity, which appeared to be the case in our study as well.…”
Section: Discussionsupporting
confidence: 87%
“…Such a protein engineering problem presents substantial challenges, which can in principle be overcome by molecular evolution. Therefore, we chose to deploy PACE, a rapid evolution system 35 , which has been used to evolve RNAP promoter specificity, protein-DNA interactions, protease activities, and protein-protein interactions 3,30,3540 . Briefly, PACE involves providing an evolving gene of interest to M13 bacteriophage, linking the life cycle of the phage to a desired activity of interest to be evolved in the target gene, and then propagating the virus until the activity evolves.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed selection pressures, indicated by listing multiple posAP/negAP sets for a given timepoint, were utilized as appropriate to enhance the likelihood of successful evolution. 24,30,40 …”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that PACE can experimentally explore the effects of mutation rate and selection stringency on evolutionary outcomes (23). In this work, we used PACE to experimentally address the following questions: (i) If initially identical enzyme populations are subjected to distinct selection pressures before converging toward a common evolutionary goal (Fig.…”
mentioning
confidence: 99%